A review of factors associated with maintenance of sinus rhythm after elective electrical cardioversion for atrial fibrillation. Issue 6 (7th June 2018) - Ecker, Veronika; Knoery, Charles; Rushworth, Gordon; Rudd, Ian; Ortner, Astrid; Begley, David; Leslie, Stephen J.
Abstract : Atrial fibrillation is the most common heart‐rhythm disorder, affecting about 1.5% to 2% of the population with an increased risk of mortality and morbidity due to stroke, thromboembolism, and heart failure. If the conversion back to sinus rhythm does not happen spontaneously, pharmacological or electrical cardioversion (ECV) is the next available treatment options for some patients. However, the long‐term success following ECV is variable. This review describes the factors that are associated with maintenance of sinus rhythm following ECV and proposes a clinical strategy based on the available evidence.